A randomized double‐blind controlled trial of different filling pressures in operative outpatient hysteroscopy. Issue 1 (25th July 2017) - Haggag, Hisham; Hassan, AbdelGany; Wahba, Amr; Joukhadar, Ralf
Abstract: Objective: To identify the optimal filling pressure during operative outpatient hysteroscopy that allows completion of the procedure while minimizing pain. Methods: A double‐blind randomized controlled trial of women aged 20–60 years undergoing operative hysteroscopy (including biopsy sampling, polypectomy, septum excision, adhesiolysis, or intrauterine device removal) was undertaken at a university hospital in Egypt between May 2014 and July 2016. Using a computer‐generated randomization sequence, patients were randomly assigned into three equal groups: filling pressures of 40 mm Hg (group 1), 60 mm Hg (group 2), and 80 mm Hg (group 3; control). The primary outcome was the proportion of successfully completed procedures. Analyses were by intention to treat. Results: Each group contained 80 women. The procedure was completed for 63 (79%) women in group 1, 73 (91%) in group 2, and 76 (95%) in group 3 ( P= 0.004). The proportion of completed procedures in group 3 was significantly different from that in group 1 ( P= 0.002), but did not differ significantly from that in group 2 ( P= 0.349). Conclusion: A uterine filling pressure of 60 mm Hg does not reduce the frequency of completion when compared with 80 mm Hg in operative outpatient hysteroscopy. ClinicalTrials.gov registration: NCT02142673. Abstract : Procedure completion with a 60 mm Hg filling pressure was as frequent as with 80 mm Hg. Use of 60 mm Hg could reduce pain.